Assessing the sustainable development of rural tourism destination using ecosystem service value index : The case of Yanyang Town, Guangdong, China - Zhimin, Wang (2024)
The explosive development of rural tourism in China inevitably damages the rural environment, making the sustainable development of rural tourism destinations an urgent problem. This study aims to evaluate the sustainable development status of rural tourism destinations, examine how rural tourism affects rural ecosystems, and determine the sustainable development path. Based on the village samples of different development modes and stages (2004, 2014, and 2020), this study adopted quantitative methods such as case comparison and geographical research methods to analyze the temporal and spatial variation characteristics of ecosystem service value (ESV) in Yanyang Town, a typical rural tourism town, under the tourism-driven land use change. Then, each study problem is thoroughly examined using ESV as the primary index. The findings of the study indicate that: (1) Forests are the dominant land use in Yanyang Town, providing ecosystem support and contributing to ESV. Changes in forest land determine ecosystem trends. (2) Over the past 16 years, total ESV decreased by 7.19 million yuan, showing an initial decline followed by an increase corresponding to different development stages of rural tourism. While total ecoeconomic harmony has improved, a serious crisis remains, indicating unsustainable development in Yanyang Town. (3) The primary impact of rural tourism on ecosystems is through changes in surface land structures. Compared to traditional agriculture, rural tourism has a more positive effect on ecosystems and causes less disruption to the land. However, its impact varies depending on the stages and modes of development. (4) Human activities, elevation and slope, are the main factors influencing spatial variations in ESV in Yanyang Town. The ecosystem is also affected by other natural and economic factors, with their influence varying by location. In conclusion, the study demonstrates that while rural tourism can revitalize and sustain rural areas, it is essential to protect ecosystems by minimizing land disturbances and conserving forests. A more sustainable and thoughtful approach to rural tourism is needed. Additionally, the findings highlight that the ESV index is a useful tool for assessing rural sustainability and can help guide the development of rural tourism destinations.